Intention to participate in tax evasion: a survey of accounting and non-accounting background employees - Noral Hidayah Alwi; Bibi Nabi Ahmad Khan; Zahir Osman (2023)
Tax evasion is still justified by Malaysian citizens as being tolerable and acceptable, as seen by the greater number of tax evasion cases and rise in unpaid tax figures in the country. This study examines the connection between attitude, perceived behaviour control and subjective norms towards tax evasion behaviour between the accounting and non-accounting background. (Abstract by authors)